2008
DOI: 10.1083/jcb.200805132
|View full text |Cite
|
Sign up to set email alerts
|

PSD-95 promotes synaptogenesis and multiinnervated spine formation through nitric oxide signaling

Abstract: Postsynaptic density 95 (PSD-95) is an important regulator of synaptic structure and plasticity. However, its contribution to synapse formation and organization remains unclear. Using a combined electron microscopic, genetic, and pharmacological approach, we uncover a new mechanism through which PSD-95 regulates synaptogenesis. We find that PSD-95 overexpression affected spine morphology but also promoted the formation of multiinnervated spines (MISs) contacted by up to seven presynaptic terminals. The formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
132
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 157 publications
(149 citation statements)
references
References 45 publications
16
132
1
Order By: Relevance
“…We analyzed PSD95 expression in hippocampal area CA1 after contextual fear conditioning and show that only under a condition that leads to LTM formation is there a pronounced training-induced PSD95 overexpression in the T286A mutants. Thus, the persistent increase in MIS in T286A mutants accompanies training-induced PSD95 overexpression in agreement with the hippocampal slice culture experiments (21). We show also that the training-induced PSD95 overexpression in T286A mutants is blocked by the mTOR inhibitor rapamycin.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…We analyzed PSD95 expression in hippocampal area CA1 after contextual fear conditioning and show that only under a condition that leads to LTM formation is there a pronounced training-induced PSD95 overexpression in the T286A mutants. Thus, the persistent increase in MIS in T286A mutants accompanies training-induced PSD95 overexpression in agreement with the hippocampal slice culture experiments (21). We show also that the training-induced PSD95 overexpression in T286A mutants is blocked by the mTOR inhibitor rapamycin.…”
Section: Discussionsupporting
confidence: 90%
“…The postsynaptic scaffolding protein PSD95 has been linked with synaptogenesis (20). Furthermore, in hippocampal slice cultures overexpression of PSD95 leads to MIS formation, in particular (21). This fact, together with our finding that contextual LTM in T286A mutants is linked with synaptogenesis including persistent MIS generation, suggested that PSD95 overexpression is involved in memory formation in T286A mutants.…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…NR2B‐rich NMDARs suppress prosurvival CREB‐mediated gene expression by activating PSD95/nNOS signaling (Martel et al., 2012; Soriano et al., 2008). However, PSD95‐nNOS interaction is critical for synaptic connections (Nikonenko et al., 2008), and therefore, prolonged suppression of PSD95‐nNOS interaction may lead to unknown risks.…”
Section: Introductionmentioning
confidence: 99%